AKIBAT HUKUM PEMBERI KERJA MEMFASILITASI PENERJEMAH BAGI TENAGA KERJA ASING - Wawan Haryanto (Al-Amwal : Journal of Islamic Economic Law, 2022)
Foreign workers are generally not able to speak Indonesian so some foreign worker employers facilitate foreign workers with interpreters. considering that interpreters are very helpful in bridging communication between foreign workers and local workers. However, on the other hand, the main obligation of employers of foreign workers related to language issues is to facilitate Indonesian language education and training for foreign workers. This study uses a normative method with library research data collection techniques. The results show that in the provisions for the use of foreign workers, there is no obligation for employers to facilitate foreign workers with interpreters, besides that there is also no prohibition for employers of foreign workers to facilitate interpreters, this then shows that there are no explicit provisions regulates the position of interpreters in accompanying foreign workers so that the involvement of translators accompanying foreign workers does not have legal consequences for employers who employ foreign workers.